Determination of Trace Nickel in Spinach Samples Using the Combination of Vortex-assisted Deep Eutectic Solvent-based Liquid Phase Microextraction and Slotted Quartz Tube - Flame Atomic Absorption Spectrometry - Alacakoc, Bihter; Tekin, Zeynep; Unutkan, Tugce; Cetin, Gulten; Bakirdere, Sezgin (ATOMIC SPECTROSCOPY PRESS LTD, 2019)
A novel, green, and efficient analytical method was developed for the preconcentration of nickel in spinach samples, prior to the determination by slotted quartz tube (SQT) - flame atomic absorption spectrometry (FAAS). Diphenylcarbazone was employed as the ligand, and a deep eutectic solvent (DES)-based liquid phase microextraction (LPME) was used to enrich the analyte for its determination at trace levels. All parameters of the SQT-FAAS and DES method were systematically optimized to enhance the detection power of conventional FAAS. Under the optimum experimental conditions, the optimized method (DES-LPME-SQT-FAAS) recorded a 60-fold improvement in detection power over the FAAS. The limits of detection and quantification were 3.8 and 12.6 mu g L-1, respectively. The calibration plot was linear over a wide concentration range, and the precision for replicate measurements was appreciably high. Nickel was not detected in the spinach samples analyzed, but the spiked recovery tests for three samples yielded results close to 100%, confirming the method's accuracy and applicability to this type of matrix.
Keywords: PRECONCENTRATION SYSTEM; FOOD SAMPLES; WATER; Spectroscopy